Robust In Vitro Pharmacology of Tmod, a Synthetic Dual-Signal Integrator for Cancer Cell Therapy - Manry, Diane; Bolanos, Kristian; DiAndreth, Breanna; Mock, Jee-Young; Kamb, Alexander (Frontiers in Immunology, 2022)
Progress toward improved solid-tumor treatment has long been hindered by the lack of truly tumor-specific targets. We have developed an approach to T cell therapy based on a dual-receptor system called TmodTM that addresses this problem. The Tmod system exploits one of the few common genetic differences between tumor and normal cells: loss of heterozygosity (LOH). It utilizes the basic mechanistic logic that evolved in early vertebrates to mediate self vs. non-self discrimination, where an activation stimulus is blocked by self-ligands. Tmod constructs employ a chimeric antigen receptor (CAR) or T cell receptor (TCR) as activator component and a modified LIR-1 inhibitory receptor (blocker) to achieve high selectivity based on expression of the blocker antigen (Ag). Here we explore the in vitro pharmacology of a blocker directed at the HLA-A*02 Ag paired with either a mesothelin CAR or an HLA-A*11-restricted KRAS peptide TCR. While more sensitive to receptor expression changes on effector cells, we show that Tmod response is well-buffered against variations in Ag levels on target cells. In addition, the data reveal at least two distinguishable pharmacologic mechanisms of Tmod blocker function: (1) reducing activator sensitivity and (2) decreasing activation magnitude.